Household Pharmaceutical Disposal Practices, Community Understanding, and Readiness for Medicines Take-Back in Asmara, Eritrea: A Cross-Sectional Analysis - Habte HY; Bahta M; Russom N; Kibreab F; Andemariam A; Tewelde T; Russom M (Dove Medical Press, 2024)
Heaven Yohannes Habte,1 Merhawi Bahta,1 Natnael Russom,1 Fitsum Kibreab,2 Adiam Andemariam,3 Tomas Tewelde,4 Mulugeta Russom1,5,6 1National Medicines and Food Administration, Ministry of Health, Asmara, Eritrea; 2Health Research and Resources Centre Division, Ministry of Health, Asmara, Eritrea; 3Zoba Maekel Pharmaceutical Service, Ministry of Health, Asmara, Eritrea; 4Orotta College of Medicine and Health Science, Department of Medical Science, Unit of Pharmacy, Asmara, Eritrea; 5Department of Medical Informatics, Erasmus Medical Center, Rotterdam, Netherlands; 6European Programme for Pharmacovigilance and Pharmacoepidemiology, University of Bordeaux, Bordeaux, FranceCorrespondence: Natnael Russom, National Medicines and Food Administration, Ministry of Health, Asmara, Eritrea, Tel +291-7602351, Email natiraesi@gmail.comIntroduction: Unused and/or expired pharmaceuticals stored in households are potential health and environment hazards that require safe disposal. In Eritrea, there has not been a proper household medicines disposal system and pharmaceutical wastes had been disposed of irrationally. The study was therefore conducted to assess community's understanding and disposal practices of unused/expired medications and willingness to participate in a household medicines take-back system.Methods: A cross-sectional study was conducted from January to February 2023 in randomly selected households of Asmara. The study participants were selected using a multi-stage-cluster sampling. Data, collected through face-to-face interview using a structured questionnaire, were double entered using CSPro version 7.3 software package and analyzed using SPSS version 26.Results: A total of 327 participants were enrolled in the study with a predominance of female respondents (84%). The most commonly used disposal practices were throwing with household garbage (65.6%), followed by dumping under soil (38.7%) and flushing down the toilet/sink (15.2%). Around three-quarters (70.5%) of the households had unused/expired medicines stored at home during the data collection period with intention to use being the most common reason for storage (83.9%). Analgesics and anti-infectives were the most commonly stored classes of medicines, and more than half of the anti-infectives were stored for future use. The mean knowledge score of participants was 7.31/11 (95% CI: 7.09- 7.52). Moreover, participants had a satisfactory willingness to participate in a household medicines take-back system, with a mean attitude score of 16.89/20 (95% CI: 16.45- 17.29). Lack of awareness, negligence, time/health constraints, fear of accountability/stigma, accessibility and reluctance were reported as possible challenges in establishing a household medicines take-back system.Conclusion: Unnecessary storage and improper disposal of household unused/expired medicines along with inadequate knowledge on disposal mechanisms were common in households of Asmara. Hence, public education on proper disposal as well as coordinated efforts for the establishment of safe disposal mechanisms are recommended.Keywords: household disposal practices, expired, unused, medicines take-back, pharmaceuticals, knowledge, willingness, Asmara